Desenvolvimento e aplicação de fibras capilares em espectrometria de massas ambiente com ionização por spray de toque (TSI-MS) - Allochio Filho, João Francisco (2021)
In recent years, technological development in the field of analytical instrumentation has progressed vigorously, which has allowed the evolution of analytical techniques that play an indispensable role within society, highlighting the mass spectrometry (MS). Parallel to the technological advance of this technique, the development of new ionization methods that are simpler, faster and that allow a direct analysis without the need for prior treatment or sample processing is underway. The methods of ambient ionization derived from paper spray have been developing rapidly today mainly in forensic analysis field due to the chemical modifications made in the paper substrate and the introduction of new types of organic materials that function as a probe/substrate to collect, store, and ionize the sample, then enabling more efficient and selective analyses. In this work, an ambient analysis method was developed using capillary polymeric fibers that acted as a probe/substrate in the direct detection of illicit substances by diving the fiber directly into the sample, thus performing an in natura analysis that preserves the chemical profile of the components present in the sample. The method was tested and compared in parallel using PSI-MS experiments, presenting satisfactory results for the detection and determination of cocaine in whole blood and urine. For example, LOD and LOQ of 32.0 and 106.7 ng/mL were obtained for the use of fiber in the determination of cocaine in blood, compared with LOD and LOQ vales of 58.8 and 195.8 ng/mL obtained with the use of cellulosic paper as substrate; as well as LOD and LOQ values of 5.16 and 17.21 ng/mL achieved for determination of cocaine in whole urine from fiber spray compared to LOD and LOQ values of 5.73 and 19.09 ng/mL obtained for paper spray. Furthermore, our method was able to detect with good mass accuracy and sensitivity many chemical components such as THC, ecstasy (MDMA), NBOMe's, opioids, among other illicit substances present in samples of seized drugs, e.g., hashish, seals, tablets, and powder, as well as was efficient in detecting cocaine and its metabolites in real blood and urine samples from drug abuse event. The fiber spray ionization method (FSI-MS) developed in this work was able to be applied in blood and urine analyses with efficiency and good sensitivity, representing an excellent analytical alternative within the ambient ionization techniques, especially in experiments based on touch spray ionization (TSI-MS).